Associations Between Self-Reported Sleep, Wellbeing and Physical Activity in Irish Adolescents - Murphy, John; Sweeney, Mary Rose; O’Hagan, Anna Donnla; McGrane, Bronagh (European Scientific Journal, ESJ, 2022)
Growing evidence suggests sleep plays an important role in the development of healthy adolescents, with increased interest in the associations between sleep and mental health. Higher duration and quality of sleep has been suggested as a mechanism for increased wellbeing in adolescents. Cross sectional data was collected from 5,661 Irish adolescents. 55% of Irish adolescents reported meeting the guidelines for adolescents of 8-10 hours per night. This was found to decrease with age. Higher duration and quality of sleep was positively associated with wellbeing and negatively associated with symptoms of anxiety and depression. A higher frequency of physical activity was associated with longer duration and higher quality of sleep. 9-10 hours of sleep was associated with the highest levels of wellbeing and lowest symptoms of anxiety and depression. The relationship between physical activity and increased wellbeing may be impacted by physical activity leading to higher durations and quality of sleep. Higher frequencies of physical activity may increase sleep quality and quantity thereby improving markers of mental health in adolescents.